PENYEBARAN SEMUT PADA HUTAN LINDUNG SIRIMAU KOTA AMBON - Fransina Sarah Latumahina; Musyafa Musyafa; Sumardi Sumardi; Nugroho Susetya Putra (Environmental Research Center (PPLH) of Udayana University, 2014)
The experiment was conducted at residential areas Sirimau forest with three sampling methods,which were hand collecting, bait trap (sugar and tuna) and pitfall traps from July to September2011. The study aims to determine diversity of ants in residential areas in Ambon SirimauProtected Forest areas. The results of study found 16 species of ants in total reaching 14.913.The most dominant types are Odontoponera denticulata, Pheidole megacephala,Technomyrmex albipes, Tetramorium simillimum, Tetramorium bicarinatum, Tapinomamelanocephalum, Paratrechina longicornis and Anoplolepis gracilipes. Total diversity ofants is 2.789 classified as moderate by spread of number of individual spread and of communitystability. The diversity of ants is strongly influenced by light intensity, temperature, humidity,wind, water and season. Difference of temperature micro, light climate, humidit, interspecificcompetition, availability of variety of food sources, habitat quality and human activities alsoaffect the diversity of ants. Another finding showed invasive ants, they were Soleonopsisgeminate, Paratrechina longicornis and Anoplolepis gracilipes.